Psychometric properties of the spanish version of the civic behavior scale (2017)
The purpose of this study is to present the psychometric properties of a Spanish version of the Civic Behavior Scale (CBS) a new instrument developed by the authors that measure the perceived civic behaviors of faculty members and white-collar workers in a Higher Education Institution. For this purpose, 538 students of a University in Ecuador responded to CBS. Confirmatory factor analysis using structural equation modeling revealed that the questionnaire shows a high reliability (a=0.95) and convergent and discriminant validity and that can be used by researchers and practitioners to assess civic behaviors in educational institutions. Other results, contributions and limitations of the present study are discussed. © 2017 revistaESPACIOS.com.